Pengetahuan Pengasuhan, Maternal Self-Efficacy, Praktik Pengasuhan, Riwayat Kelahiran, dan Perkembangan Motorik Anak Baduta - Iftitahun Nabilah; Dwi Hastuti; Melly Lathifah (AWLADY : Jurnal Pendidikan Anak, 2022)
The influence  of birth history and mother's parenting to motor development have been widely studied. However the importance of parenting knowledge and maternal self-efficacy is not yet clear. This study aims to analyze the effect of parenting knowledge, maternal self-efficacy, parenting practices and birth history to motor development of children aged 1-2 years old. This research is explanatory. The research location was chosen purposively in 5 selected villages is Panggang city, Karangturi city, Wonorejo city, Glagah city, Konang city, in Glagah sub-district in Lamongan city .  The population of this study was family has children aged 12-24 months, and from 5 selected villages, 104 children were obtained. The data collected using the self-report method and analyzed using Structural Equation Modelling (SEM). Results of this study showed that parenting practice (β=4.308; t>1.96) had a positive effect to motor development of children. Parenting practice influenced by maternal self-efficacy (β=3.861; t>1.96), and maternal self-efficacy influenced by parenting knowledge (β=3.472; t>1.96). Parenting knowledge had a specific indirect effect to motor development through maternal self-efficacy and parenting practice (β=2.043;t>1.96).. Parenting knowledge had a specific indirect effect to parenting practice through maternal self-efficacy  (β= 2.319; t>1.96). Maternal self-efficacy had a specific indirect effect to motor development through parenting practice (β= 2.685; t>1.96).